Assessment of Similarity Rates of Liver Images Using Geometric Transformations - Palabas, Tugba; Osman, Onur; Ergin, Tuncer; Teomete, Uygar; Dandin, Ozgur; Aydin, Nizamettin (IEEE, 2015)
In this study, similarity rates of the liver images are determined using 3D geometric transformation methods and numerical comparisons are made. Three geometric transformation methods scaling, rotating, and translating are consecutively applied to 10 intact liver images which are drawn by the radiologists. Atlases of liver images are generated, Dice coefficients are calculated according to the specified atlases and are assessed for various cases. This study is presented as a step to prepare atlas database for segmentation of the injured liver.
Keywords: geometric transformation; injured liver; segmentation; Dice coefficient; MULTIORGAN SEGMENTATION; CT; ENHANCEMENT; SHAPE; Computer Science